2022
DOI: 10.1590/1807-1929/agriambi.v26n9p649-654
|View full text |Cite
|
Sign up to set email alerts
|

Chickpea seed storage in different packagings, environments and periods

Abstract: Storage is a fundamental practice in the control of the physiological quality of seeds, as it is a method that can preserve their viability and vigor for a longer period. Thus, the objective of the present study was to evaluate the storage of chickpea seeds in different packagings, environments, and periods. The completely randomized design was used in a 2 × 2 × 4 factorial scheme, corresponding to two types of packaging (hermetic and Kraft® paper), two storage environments (cold chamber environment and conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 16 publications
2
6
0
1
Order By: Relevance
“…In contrast, the moisture content in the hermetic bags remained at safe storage levels throughout the entire 6‐month storage period. These findings align with previous studies that have demonstrated the effectiveness of hermetic bags in maintaining stable seed moisture content 14,15,18,36 . Similar results have been reported for other crops, such as green grams, where moisture content increased in PP and jute bags but remained consistent in hermetic bags over a 6‐month storage period 37 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In contrast, the moisture content in the hermetic bags remained at safe storage levels throughout the entire 6‐month storage period. These findings align with previous studies that have demonstrated the effectiveness of hermetic bags in maintaining stable seed moisture content 14,15,18,36 . Similar results have been reported for other crops, such as green grams, where moisture content increased in PP and jute bags but remained consistent in hermetic bags over a 6‐month storage period 37 .…”
Section: Discussionsupporting
confidence: 91%
“…maculatus , C. analis , Acanthoscelides obtectus , and Bruchus incarnates , which cause a significant loss in chickpea grain 4 . Understanding environmental factors during storage is crucial for making informed decisions and minimize quality losses 18 . Environmental variables such as temperature, RH, and seed moisture content should be considered during storage because unfavorable conditions could diminish seed lifetime 31 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nas nossas condições, as informações são ainda restritas, predominando o cultivo de grão-de-bico do tipo kabuli. Silva et al (2022), ao armazenarem sementes do tipo kabuli com 10,6% de umidade em sacos de papel e embalagem hermética sob condições não controladas de ambiente e câmara fria (14,5 ºC e 65% UR), observaram que a germinação das sementes decresceu linearmente em ambas as condições, independente da embalagem. A germinação inicial que era de 83% caiu para valores na faixa de 42% após 90 dias.…”
Section: Introductionunclassified